Analysis of IMOD-Based Poetry Reading Ability in Grade V Students: Analisis Kemampuan Membaca Puisi Berbasis IMOD pada Siswa Kelas V SD - Safitri, Rina Eka; Fatayan, Arum (Indonesian Journal of Innovation Studies, 2025)
General Background: Reading skills are a fundamental component of language learning in elementary education, particularly for developing students’ cognitive and affective abilities. Specific Background: Poetry, as a distinct literary form, demands specialized techniques for interpretation and expression, making it a challenging yet valuable medium in language instruction. Knowledge Gap: However, students often struggle with poetic comprehension and expression due to the lack of effective pedagogical strategies tailored to poetry reading. Aims: This study aims to analyze the implementation and effectiveness of the IMOD (Imitation Model) method in enhancing the poetry reading skills of fifth-grade elementary students. Results: Using a qualitative case study approach involving classroom observations, interviews, and documentation, the research found that IMOD significantly improved students' engagement and interpretative performance, especially for poems themed "my teacher", "my mother", and "my father". Novelty: The novelty of this research lies in demonstrating the practical integration of modeling techniques in poetry instruction, which fosters active participation and expressive reading among students despite limited learning facilities. Implications: These findings highlight the necessity of innovative and experiential teaching models in language education and suggest that structured imitation can be a powerful tool to cultivate poetic literacy in young learners.Highlight : IMOD (Imitation Model) method effectively enhances students’ poetry reading skills through modeling by teachers. The approach increases student engagement despite limited learning facilities. Implementation involves clear planning, expressive reading, and overcoming technical and performance challenges. Keywords : Poetry, Imod Method, Indonesian Language Learning, Elementary School, Reading Skills